The HITRAN 2012 molecular spectroscopic database; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 130 - Rothman R. S.; Gordon I. E.; Babikov Y.; Barbe A.; Chris Benner D.; Bernath P. F; Birk M.; Bizzocchi L.; Boudon V.; Brown L. R.; Campargue A.; Chance K.; et al. (2013, 2013)
Title screen